To Admit or Not to Admit: That is the Cleft Lip Question. Confirming the Safety of Outpatient Cleft Lip Repair. Issue 1 (July 2018) - Fahradyan, Artur; Galdyn, Izabela; Azadgoli, Beina; Tsuha, Michaela; Urata, Mark M.; Francis, Stacey H.
Abstract : Background: There is no accepted protocol for inpatient versus ambulatory cleft lip surgery. The aim of this study was to review the safety of outpatient repair and develop guidelines. Methods: A retrospective review of patients younger than 2 years undergoing primary cleft lip repair from 2008 to 2015 at six centers was performed. Patients were divided into two groups: predominantly ambulatory (discharged or admitted for specific concerns) and inpatient (admitted due to surgeon's preference). The impact of independent variables on admission, emergency department visits, and readmission within 1 month of discharge was analyzed. Results: Of 546 patients, 68.1 percent were boys, 4.4 percent had syndromes, and 23.6 percent had comorbidities. One hundred forty-two patients were admitted postoperatively. Forty-nine admissions were attributable to the surgeon's preference. After excluding this subset, our ambulatory surgery rate was 81 percent. There was no difference in emergency department visits (3 percent versus 2.2 percent; p = 0.6) or readmissions (0 percent versus 1.45 percent; p = 0.5) between groups. None of the ambulatory surgery patients were readmitted within 36 hours, for a successful ambulatory surgery rate of 100 percent. Female sex; surgical time; prematurity and/or postconceptional age younger than 52 weeks; and cardiac, respiratory, central nervous system, gastrointestinal, genitourinary, and other congenital comorbidities had significant impact on admission rates in the predominantly ambulatory group ( p < 0.05). Respiratory comorbidities and syndromes were risk factors for readmission if patients presented to the emergency department ( p < 0.05). Conclusions: Ambulatory cleft lip repair can be performed safely in most patients with no difference in emergency department visits or readmission. Patients with comorbidities should be admitted for observation. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : This and Related "classic" Articles Appear on Prsjournal.com for Journal Club Discussions.Patient Safety CME.